إعداد مادة تعليم مهارة الكتابة على أساس الأنماط اللغوية (بحث تطويري لمادة الكتابة 1 لطلبة قسم تعليم اللغة العربية بجامعة سونن أمبيل الإسلامية الحكومية سورابايا) - Bahauddin, Bahauddin (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2017)
This paper is aimed to arrange teaching material for writing which will enable students to enhance their writing ability by arranging sentences through language pattern (al-anmat al-lughawiyyah). For this purpose to achieve, it is formulated three research questions as follows: 1) how is the composition of teaching material for writing skill that is based on language pattern for PBA students of UIN Sunan Ampel Surabaya, 2) how is that teaching material of writing that is based on language pattern implememented for students of PBA department UIN Sunan Ampel Surabaya, 3) to what extent is the effectiveness of the teaching material implementation to enhance the ability of arranging sentences through language pattern among the students of PBA department UIN Sunan Ampel Surabaya.To answer all those questions, this study employes mixed methods: quantitative through descriptive analysis approach, research and development (R&D), and also the experimental one. Indeed, it aims to examine the effectiveness of students'exercise score based on their pre and post test. Besides, as the population taken is 2nd semester students of PBA department of UIN Sunan Ampel Surabaya, it was taken 19 of them to be the samples of this study. At the end, this study shows that the proposed hypothesis is acceptable. It however means that the implementation of teaching material designed to enhance students' writing skill through language pattern is effective for students of PBA department UIN Sunan Ampel Surabaya. As counted, the result of pretest was 7.15 and 7.94 for the post test. It fruitfully means that the teaching material that is developed through language pattern is effective to enhance students'writing ability